Perancangan Sistem Monitoring Jaringan Berbasis Web Menggunakan Simple Network Management Protocol (SNMP) (Studi Kasus: UPT TIK Universitas Riau) - Nur Aprilia Sari; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Information and Communication Technology Integrated Services Unit (UPT TIK) is an unit in the University of Riau which is engaged in the service and management of everything related to information technology. UPT TIK manages network devices such as routers and switches that are scattered in every faculty/ institution building in the University of Riau. Network administrator who monitors the network equipment. Currently, the monitoring process uses the Cisco switches at UPT TIK by checking the devices one by one. This monitoring process is deemed ineffective because there are many devices unmanagable scattered in every faculty/institution building at the University of Riau so that administrator have difficulty checking the state of the devices whether they are connected or not. In this study, the design and implementation of the SNMP protocol for network management was carried out directly at the UPT TIK University of Riau. A monitoring system can also be called a Network Management System, which is a system that functions to assist network administrator in monitoring and controlling network devices. SNMP is anapplication protocol on a TCP / IP network that can be used as a protocol in Network Management System. The development of this system uses the PHP Programming Language and the MySQL database management system. From the results of system testing and analysis, it is found that the monitoring and network management systems that have been designed can run well in monitoring network devices. Keywords : Network Administrator, Monitoring, Network Management System, SNMP, Network Devices.